Chemical Pulping of Mustard Straw - Karira, B. G.; Dhawan, Rita (Indian Forester, 1989)
Chemical pulps (35-41% unbleached yield) consistent with good strength characteristics were produced from mustard straw using soda process. It was observed that mustard straw requires more drastic digestion conditions than rice straw and wheat straw. The data on proximate chemical composition and fibre dimensions of mustard straw is also recorded in this article.